Postischemic cardiac recovery in heme oxygenase-1 transgenic ischemic/reperfused mouse myocardium - Juhasz, Bela (Blackwell Publishing Ltd, 2011)
Heme oxygenase-1 (HO-1) transgenic mice (Tg) were created using a rat HO-1 genomic transgene. Transgene expression was detected by RT-PCR and Western blots in the left ventricle (LV), right ventricle (RV) and septum (S) in mouse hearts, and its function was demonstrated by the elevated HO enzyme activity. Tg and non-transgenic (NTg) mouse hearts were isolated and subjected to ischemia/reperfusion. Significant post-ischemic recovery in coronary flow (CF), aortic flow (AF), aortic pressure (AOP) and first derivative of AOP (AOPdp/dt) were detected in the HO-1 Tg group compared to the NTg values. In HO-1 Tg hearts treated with 50 μmol/kg of tin protoporphyrin IX (SnPPIX), an HO enzyme inhibitor, abolished the post-ischemic cardiac recovery. HO-1 related carbon monoxide (CO) production was detected in NTg, HO-1 Tg and HO-1 Tg + SnPPIX treated groups, and a substantial increase in CO production was observed in the HO-1 Tg hearts subjected to ischemia/reperfusion. Moreover, in ischemia/reperfusion-induced tissue Na(+) and Ca(2+) gains were reduced in HO-1 Tg group in comparison with the NTg and HO-1 Tg + SnPPIX treated groups; furthermore K(+) loss was reduced in the HO-1 Tg group. The infarct size was markedly reduced from its NTg control value of 37 ± 4% to 20 ± 6% (P < 0.05) in the HO-1 Tg group, and was increased to 47 ± 5% (P < 0.05) in the HO-1 knockout (KO) hearts. Parallel to the infarct size reduction, the incidence of total and sustained ventricular fibrillation were also reduced from their NTg control values of 92% and 83% to 25% (P < 0.05) and 8% (P < 0.05) in the HO-1 Tg group, and were increased to 100% and 100% in HO-1 KO(−/−) hearts. Immunohistochemical staining of HO-1 was intensified in HO-1 Tg compared to the NTg myocardium. Thus, the HO-1 Tg mouse model suggests a valuable therapeutic approach in the treatment of ischemic myocardium.